Mechanistic insights into the anticancer, anti-inflammatory, and antioxidant effects of yellowfin tuna collagen peptides using network pharmacology - Kairupan, Tara S.; Kapantow, Nova H.; Tallei, Trina E.; Niode, Nurdjannah J.; Sanggelorang, Yulianty; Rotty, Linda WA.; Wungouw, Herlina IS.; Kawengian, Shirley ES.; Fatimawali, Fatimawali; Maulydia, Nur B. (Narra J, 2025)
Marine-derived collagen peptides have been acknowledged for their therapeutic potential, especially in cancer therapy and inflammation management. The aim of this study was to investigate the molecular mechanisms that contribute to the anticancer, anti-inflammatory and antioxidant properties of yellowfin tuna collagen peptides (YFTCP) utilizing a network pharmacology approach. The YFTCP was extracted from the bones of yellowfin tuna (Thunnus albacares) and subsequently hydrolyzed with trypsin. Seventeen peptides were discovered using liquid chromatography in conjunction with high-resolution mass spectrometry (LC-HRMS). A network pharmacology method was utilized to investigate the interactions between the discovered peptides and their biological targets. Additionally, gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed to identify pertinent biological pathways involved in the anticancer, antioxidant, and anti-inflammatory effects of these peptides. GO analysis revealed key associations between YFTCP and critical cancer- and inflammation-related genes encoding proteins such as CCND1, SRC, AKT1, IL-1β, TNF, and PPARG, which exhibited significant interactions. These proteins are essential for the regulation of the cell cycle, the development of tumors, and the response to inflammatory stimuli. The KEGG analysis also revealed that YFTCP was involved in a number of critical pathways, such as endocrine resistance, cancer pathways, Kaposi sarcoma-associated herpesvirus infection, proteoglycans in cancer, and human cytomegalovirus infection. These findings highlight the potential use of YFTCP as a multifaceted therapeutic agent, indicating their role in regulating important biological pathways associated with cancer development and inflammation. This study provides new valuable insights into the pharmacological properties of YFTCP, paving the way for future studies and drug development focused on these bioactive peptides.